The characteristic of frequency response on winding faults and configurations of transformer - Md. Yasid, Nurul Farahwahida (2019)
This research presents a study on the monitoring of several winding configurations of power transformers using Frequency Response Analysis (FRA). The frequency response provides indications of any mechanical and electrical changes in the transformer’s active parts. Three units of three-phase transformers were tested with the aim to investigate their FRA responses due three case studies. They are due to vector group, three types of faulty winding and also the effect of coupling in the three-phase core-typed transformers. The tests were repeated to Dyn11 360VA, 100kVA and 500kVA core-typed transformers to carry out the desired condition scenario of the FRA responses. Transformer Turn Ratio (TTR) and winding resistance test are performed to establish the present condition of the transformers winding. The TTR test is conducted to determine the turn ratio of high voltage (HV) to the low voltage (LV) windings at no load condition. Meanwhile, winding resistance test is performed to check for gross difference between the windings. From these test results, it is found that the windings are in good condition. The first case is to investigate the characteristics of the FRA response due to different vector groups. It is found that it gives subtle to the response and mainly altering the medium frequency region. The second case study is the investigations of the effect of three types of faulty winding in the FRA response. They are performed by physically simulate the faults to the transformers. The faults are inter-turn short circuit (SC) fault, local overheating and radial deformation. The results show that the SC causes the starting magnitude to increase and the resonance at the low frequency region to shift towards higher frequencies. Meanwhile, during local overheating fault, the winding carries out additional resistance at the winding. It is found that it causes the alteration of the response at the very low frequency region. Lastly, the study found that radial deformation causes the responses to change in the mid-frequency region. The third case study is to investigate the effect of coupling in the three-phase transformers. This is performed by investigating the effect of fault at winding of other phases to the response of measured phase. It is found that faulty occurred in winding of other phases could actually affect the response of measured winding. The location of the fault determines how severe it is affecting the response. The findings from this research could be helpful in enriching the knowledge to evaluate the FRA response.